2017
DOI: 10.1080/10942912.2017.1349142
|View full text |Cite
|
Sign up to set email alerts
|

Odour-active compounds in baby banana Fruit (Musa acuminata AA Simmonds cv. Bocadillo)

Abstract: The contribution of individual compounds to the typical aroma of baby banana cv. Bocadillo fruit would be useful to assess aroma changes caused in the course of fruit processing. Potent odourants in baby banana fruit were determined by combined headspace solid-phase microextraction GC-Olfactometry (HS-SPME-GC-O), solvent-assisted flavour evaporation, gas chromatography−olfactometry (GC-O), gas chromatography-mass spectrometry (GC-MS), aroma extract dilution analysis (AEDA) and calculation of odour activity val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Futhermore, it is altered with the genetic makeup of fruit, cultural practices, environmental conditions, harvest maturity, postharvest handling, and storage conditions. 8 Besides, many studies reported that volatile esters are the primary components of aroma in many fruits such as peer, 44 banana, 45 pineapple, 46 and melon. 47 Olfactometry is one of the important oldest methods to assess the sensory nature of aroma in food and beverages.…”
Section: Discussionmentioning
confidence: 99%
“…Futhermore, it is altered with the genetic makeup of fruit, cultural practices, environmental conditions, harvest maturity, postharvest handling, and storage conditions. 8 Besides, many studies reported that volatile esters are the primary components of aroma in many fruits such as peer, 44 banana, 45 pineapple, 46 and melon. 47 Olfactometry is one of the important oldest methods to assess the sensory nature of aroma in food and beverages.…”
Section: Discussionmentioning
confidence: 99%
“…In apple, the main aromatic components were 1-hexanol [2]. In red-fleshed peach fruit, fruity note latone γ-hexalactone is the major aroma components [3].In banana, 2-pentyl acetate, 3-methylbutyl acetate were the most important contributors to the aroma [4]. In European pear cultivars, the volatile organic compounds mainly belong to primary esters, alcohols and alkanes [5].…”
Section: Introductionmentioning
confidence: 99%
“…In apple, the main aromatic components were 1hexanol [2]. In red-fleshed peach fruit, fruity note latone γ-hexalactone is the major aroma components [3].In banana, 2-pentyl acetate, 3-methylbutyl acetate were the most important contributors to the aroma [4]. In European pear cultivars, the volatile organic compounds mainly belong to primary esters, alcohols and alkanes [5].…”
mentioning
confidence: 99%